One hundred years of pancreatic surgery - Praderi, Raúl C (Cirugía del Uruguay, 2000)
Pancreatic surgery petains to this century. In this bief article on its histoy and, as opposed to other authors, we only refer to surgey without analysing the history of Anatomy, Histo/ogy, Physiology and Pathology of pancreas